Metastatic Anal Squamous Cell Carcinoma Presenting as an Indeterminate Biliary Stricture Diagnosed By Cholangioscopy. Issue 6 (23rd June 2022) - Nahar, Ritu; Holmes, Ian; Baliff, Jeffrey; Chiang, Austin; Kowalski, Thomas
ABSTRACT: Anal squamous cell carcinoma (SCC) rarely metastasizes outside the pelvis. Although liver involvement has been described, biliary strictures from metastatic disease are exceedingly rare. We report a case of a patient with metastatic anal SCC presenting as a biliary stricture, which was identified on endoscopic retrograde cholangiopancreatography with single-operator cholangioscopy. Direct visualization of the stricture with single-operator cholangioscopy may prove critical in obtaining a timely diagnosis. Therapeutic options for metastatic anal SCC are limited, but chemotherapy can be considered, and surgical resection is an option for limited disease.